Particularities of employing graphic means of influence in the medical advertising discourse - Tsupikova, Olena (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2025)
This article analyzes the specific use of graphic means of influence within medical advertising discourse. The analysis of factual material confirms that the effectiveness of an advertising message, as a complex multicomponent construct, is determined by the interaction between verbal and non-verbal elements. The utilization of non-verbal semiotic resources is driven by their ability to immediately appeal to the recipient’s inner world, providing a robust foundation for the effective realization of the producer’s intentions. The scope of visual (graphic) components employed in crafting advertising messages is vast and unrestricted. The article substantiates the use of graphic organizational tools, including font variations (capitalisation, fonts of different sizes and types, colour-coded letters, words, and parts of words), text localization techniques, paraphrase markers, and punctuation variations. These tools are shown to effectively capture the consumer’s attention, emphasize key text fragments, ensure ease of readability, facilitate high-quality information processing, and enhance memorability. The article demonstrates the effectiveness of font variation in highlighting key information, emphasizing significant components of the text, and accentuating specific parts or segments of words. It establishes that the use of fonts of varying sizes, such as descending gradation or alternating font sizes, creates a distinct rhythm. Different font types contribute to a positive tone, enhancing the visual appeal of the advertising text and creating a bright, attractive image. The high informational and pragmatic potential of font color is also emphasized. Bright colors enhance the message’s visibility and attractiveness, facilitate visual comprehension, and unify the text’s elements into a harmonious whole through color combinations. The highlighted media contribute to making the advertising message original, unique, and exclusive.